Separation and Purification of Four Stilbenes from Vitis vinifera L. cv. Cabernet Sauvignon Roots Through High-speed Counter-current Chromatography - Wei, Yangji; Li, Pi; Ma, Liyan; Li, Jingming (South African Journal of Enology and Viticulture, 2016)
A method for preparative separation and purification of trans-resveratrol, δ-viniferin, ε-viniferin and trans-vitisin B from the roots of Vitis vinifera L. cv. Cabernet Sauvignon was successfully established and is reported on in this paper. The four important stilbenes were purified by high-speed counter-current chromatography (HSCCC) with a suitable quaternary solvent system composed of chloroform–methanol–n-butanol–water (4:3:0.05:2, v/v). A total of 7.1 mg ± 0.2 mg of trans-resveratrol, 1.1 mg ± 0.1 mg of δ-viniferin, 18.7 mg ± 0.5 mg of ε-viniferin, and 12.2 mg ± 0.2 mg of trans-vitisin B, with purities of 97.89%, 90.61%, 94.37% and 78.38% respectively, were obtained from 241 mg of crude sample in a one-step HSCCC separation. The chemical structures of trans-resveratrol and δ-viniferin were further confirmed with the retention time using the method of standard addition, while the structural identification of ε-viniferin and trans-vitisin B was performed with LC-ESI/MS, 1H-NMR, and 13C-NMR.